Indonesian maritime threats: a preliminary study - Buddy Suseto (Penerbit Universiti Kebangsaan Malaysia, 2021)
During the Cold War era, security threats focused on the arms race between the two major powers of the world, the United States and the Soviet Union. With the end of the Cold War, this threat seemed to have changed because it involved non-military issues as well. Nevertheless, maritime issues have often become the focus of debate among scholars. Indonesia is the largest maritime country in the world and faces a variety of maritime threats. The problem is what kinds of maritime threats do Indonesia face? Based on preliminary reviews, observations in maritime seminars and open interviews with academics and government officials, this research found that the types of military and non-military threats are, among others, terrorism, sea piracy, smuggling, illegal fishing, navigation threats, asylum seekers, sea boundary problems, climate change, natural disasters and many others. These threats provide indicators of how important it is for the various agencies involved to work together in addressing the issue of maritime security threats because they pose national security problems.